Identifikasi Kanker Payudara Dengan Pendekatan Algoritma Support Vector Machine - Eko Budiarto; Mega Sholihat (DPPM Universitas Pelita Bangsa, 2025)
Breast cancer is a malignant tumor that develops in breast cells and is one of the leading causes of cancer-related deaths in Indonesia, with the highest number of patients among all cancer types. According to Globocan 2020, there were 68,858 new cases of breast cancer, representing 16.6% of 396,914 total new cancer cases in the country. The number of cases continues to rise, with 1,194 cases reported in 2021 and 1,427 cases in 2022. The increasing incidence and high mortality highlight the need for accurate early detection and classification methods. This study investigates the use of the Support Vector Machine (SVM) algorithm for classifying breast cancer. SVM was chosen due to its effectiveness in handling high-dimensional data and providing clear separation between classes. The model was evaluated using accuracy, precision, and recall metrics. The results show that SVM achieved 98% accuracy, 100% precision, and 95% recall, demonstrating strong performance in classifying breast cancer cases, minimizing false positives, and detecting the majority of positive cases. These findings indicate that SVM is a reliable method for breast cancer classification and can support medical diagnosis, facilitate early detection, and potentially reduce mortality rates. Furthermore, this approach provides a basis for developing machine learning-based clinical decision support systems in healthcare.